2015
DOI: 10.3109/09513590.2014.995617
|View full text |Cite
|
Sign up to set email alerts
|

Comprasion of ovarian stromal blood flow measured by color Doppler ultrasonography in polycystic ovary syndrome patients and healthy women with ultrasonographic evidence of polycystic

Abstract: Ovarian stromal artery Doppler examination could have an importance to explain the pathophysiology of PCOS, but there are few publications in the literature about PCOS and the details of ovarian stromal artery Doppler parameters in patients with polycystic ovarian image only. We conclude that Doppler ultrasonography findings of PCOS patients might be helpful in understanding the clinical follow-up and etiology of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In this study, we found that Preoperative 3D-TVUS features are strongly correlated with ongoing pregnancy and live birth in IUA patients after HA. With the development of ultrasonography, 3D-TVUS has been more frequently used in the field of obstetrics and gynecology (21). 3D reconstruction of the uterine anatomy provides panoramic views of the uterine cavity in the coronal plane.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that Preoperative 3D-TVUS features are strongly correlated with ongoing pregnancy and live birth in IUA patients after HA. With the development of ultrasonography, 3D-TVUS has been more frequently used in the field of obstetrics and gynecology (21). 3D reconstruction of the uterine anatomy provides panoramic views of the uterine cavity in the coronal plane.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Ozdemir et al . compared ovarian stromal blood flow with Doppler ultrasonography in patients with PCOS and healthy controls, revealing that PI was significantly different in the PCOS group ( 17 ) . In our study, we also found different PI and PSV values in the PCOS group.…”
Section: Discussionmentioning
confidence: 99%
“…Increased stromal vascularization has been shown to be prominent in polycystic ovaries particularly in CCR patients [7]. In 2015, Ozdemir et al linked this to new angiogenesis resulting from hyperplasia of ovarian theca/stromal cells secondary to elevation of LH and LH/FSH ratios [17]. Amin et al found that the increase in LH levels was correlated with vascular endothelial growth factor (VEGF) and insulin-like growth factor-1 (IGF-1).…”
Section: Discussionmentioning
confidence: 99%